Effect of drying method on the sorption isotherms and isosteric heat of persimmon pulp powder - Benedetti-Damy, P. C. [UNESP]; Pedro, M. A.M. [UNESP]; Telis-Romero, J. [UNESP]; Telis, V. R.N. [UNESP] (My University, 2010)
Moisture equilibrium data of persimmon pulp powders with 50% maltodextrin (dry basis) obtained with different drying methods were determined at 20, 30, 40 and 50°C. The spray-dryer gave a dry product with a higher adsorption capacity than the other methods. The vacuum- and freeze-dried products had the same adsorption capacity. The highest isosteric heat of sorption was observed for powders produced by spray-drying. The isokinetic temperature (TB) calculated for persimmon pulp powder obtained by vacuum-, spray- and freeze-drying were 541.4 K, 616.3 K, 513.2 K, respectively. The sorption process was spontaneous and enthalpy controlled.
Keywords: Freeze-drying; Spray-drying; Thermodynamic properties; Vacuum-drying; Water activity; Water sorption